Review Artikel Ekstrak Daun Sirsak (Annona muricata) dalam Upaya Memperlambat Pertumbuhan Sel Kanker Payudara - Marsya Marsya; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Breast cancer is the second leading cause of cancer-related deaths in women, after cervical cancer. To date, breast cancer treatment still faces various challenges, particularly in terms of effectiveness and therapy-related side effects. Therefore, alternative treatments that are safer and more effective are needed, one of which is through the use of natural ingredients such as soursop leaves (Annona muricata). This review article aims to examine the potential of soursop leaf extract in slowing the growth of breast cancer cells. Several studies have shown that soursop leaf extract contains active compounds such as acetogenin, which are known to inhibit cancer cell proliferation, induce apoptosis, and block the formation of new blood vessels (anti-angiogenesis) in cancer tissues. These bioactive compounds make soursop leaves a promising candidate for natural anticancer agents. Thus, soursop leaf extract may be considered as a complementary therapy in the management of breast cancer.